5x-11-4x=-5

Simple and best practice solution for 5x-11-4x=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-11-4x=-5 equation:


Simplifying
5x + -11 + -4x = -5

Reorder the terms:
-11 + 5x + -4x = -5

Combine like terms: 5x + -4x = 1x
-11 + 1x = -5

Solving
-11 + 1x = -5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '11' to each side of the equation.
-11 + 11 + 1x = -5 + 11

Combine like terms: -11 + 11 = 0
0 + 1x = -5 + 11
1x = -5 + 11

Combine like terms: -5 + 11 = 6
1x = 6

Divide each side by '1'.
x = 6

Simplifying
x = 6

See similar equations:

| p=4n-50 | | 6k^2+22k-8=0 | | (x+2)(x+5)=-2 | | 4w+12w-10=16w-10 | | (6+4)*2-7+9+18+(5+1*3)+5=688 | | 3(0.6+2n)-3.2=7.6 | | x(x-5)=x^2+3x+5 | | 4x+13x=102 | | x^4-9= | | (6+4)*2-7+9+18+(5+1*3)+5=x | | 2x^2=-9x | | 90x^2+1=6x | | 2.5d=0.4f+50 | | -72x^4-8x^3= | | 3(k+5)=-19 | | 15x^2-26x+8=0 | | x+9=-5x+9 | | 8y-4=3y+6 | | 8(x-8)+x=9(x-8)+8 | | (6+4)*2-7+9+18+(5+1*3)+5= | | 18x^2-50=0 | | 23x+5=15+3x | | 4(5c-1)-4=15c+7 | | 2t-8=3(t+5) | | 6n^2-21n=0 | | 3x+2x=125 | | 4(x+8)+x=-9(4-x) | | 32+2y-8=9y-11-2y | | Y+5(4y+2)=10(y+1)+9y | | 10r^2-3r-7=0 | | x+24+2x=-2-2x-9 | | 10r^2-57r+35=0 |

Equations solver categories